Physiochemical And Microbiological Analysis of Some Local Saline Soils - Mulla, Mohsin Saidnoor; Nanaware, Jayashri; Gheware, Prakash; Pathade, G.R. (Journal of Neonatal Surgery, 2025)
Crop productivity is influenced by the soil quality. Adequate quantities of macronutrients as Ca, Mg, Na, K, and Mn, as well as the biokinetic range of soil pH, and bulk density, have a profound effect on productivity; organic nitrogen and phosphorous and carbon quantities must be as per need of crop. Soil fertility is controlled by the Microbial activity. When the macronutrients cross the threshold value, the soil becomes saline; it also imbalances pH, bulk density, and Microbial activities and ultimately reduces crop productivity. Taking into account these aspects known as saline soil from Sangli, Surli, and Miraj M.S India were tested for physiochemical and microbiological properties, it was found that pH was near neutrality macronutrients at the higher side while Microbial activities w.r.t total count of bacterial, fungi, and actinomycetes, nitrogen fixers and phosphate solubilizers and organic carbon content were at the lower sides than required. The nitrogen fixing, phosphate solubilizing, and actinomycetes isolates were obtained which can be used to ameliorate saline soils so as to increase productivity of such soil.